The strategies used by English department students in giving and receiving compliments - Zatulhimmi Zatulhimmi; Asnawi Muslem (English Education Journal, 2022)
This qualitative research aims to find out the strategies used by students in giving and receiving compliments. The research participants were graduate students of English language education at Syiah Kuala University. In collecting the data, the researcher used the Discourse Completion Task (Henceforth called DCT) framework of Xiang (2013). The researcher carried out an interview adapted from Fattah (2020) to elicit participants’ understanding in conveying their compliments based on the topic complimented. The findings of DCT revealed that there were three of four types of compliment topics identified: topic appearance, topic ability/performance, and topic possession. The interview result showed that they knew how to utter compliments to each case. The responses strategies tend to use appreciation tokens consisting of 65 answers. The return consists of 11 responses, the question consists of 10 responses, the scale down consists of 8 responses, and comment history consists of 3 responses. While, praise upgrade, request, and qualification consist of 1 response, respectively. The questionnaire and DCT results were equal, which means the participants favored using appreciation tokens in giving and receiving compliments. It occurred due to their habit of daily conversation.